2005
DOI: 10.1083/jcb.200502073
|View full text |Cite|
|
Sign up to set email alerts
|

Support for the immortal strand hypothesis: neural stem cells partition DNA asymmetrically in vitro

Abstract: The immortal strand hypothesis proposes that asymmetrically dividing stem cells (SCs) selectively segregate chromosomes that bear the oldest DNA templates. We investigated cosegregation in neural stem cells (NSCs). After exposure to the thymidine analogue 5-bromo-2-deoxyuridine (BrdU), which labels newly synthesized DNA, a subset of neural precursor cells were shown to retain BrdU signal. It was confirmed that some BrdU-retaining cells divided actively, and that these cells exhibited some characteristics of SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
153
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(158 citation statements)
references
References 32 publications
4
153
0
1
Order By: Relevance
“…We grew NSCLC cell lines A549 and H441 for several passages in the presence of 1 μM BrdU, a concentration at least 200-fold below the limit at which cells take up detectable BrdU during DNA repair (23). A long pulse allowed for selection of cells that had undergone at least one symmetric division, because cells that exclusively asymmetrically divide or are senescent are "passaged out" due to expansion of symmetrically dividing cells (6,7), ensuring that both sets of DNA strands were labeled in the vast majority of cells. To address this experimentally, we stained cells at the end of the pulse with an anti-BrdU antibody and then examined them by flow cytometry and immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We grew NSCLC cell lines A549 and H441 for several passages in the presence of 1 μM BrdU, a concentration at least 200-fold below the limit at which cells take up detectable BrdU during DNA repair (23). A long pulse allowed for selection of cells that had undergone at least one symmetric division, because cells that exclusively asymmetrically divide or are senescent are "passaged out" due to expansion of symmetrically dividing cells (6,7), ensuring that both sets of DNA strands were labeled in the vast majority of cells. To address this experimentally, we stained cells at the end of the pulse with an anti-BrdU antibody and then examined them by flow cytometry and immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…The immortal DNA strand hypothesis is controversial in terms of why some cells retain their template DNA and whether or not the phenomenon is restricted to stem cells (3,4). Asymmetric division of template DNA has been shown in fibroblasts and epithelial, neural, and muscle satellite cells (1,(5)(6)(7)(8)(9)(10). Other studies have demonstrated that hematopoietic stem cells (HSCs), epidermal basal cells, hair follicle bulge cells, and intestinal epithelial stem cells segregate their chromosomes randomly (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Cela ne remet pas en cause les observation d'une ségrégation asymétrique des brins d'ADN mais soulève la question du type cellulaire capable d'effectuer la co-ségrégation du brin matrice, qui peut ne pas être une cellule souche. Des études complémentaires réalisées in vivo et in vitro ont observé une ségrégation asymétrique des brins d'ADN dans d'autres types cellulaires comme les cellules neurales [8], les cellules de la glande mammaire [9] et les cellules satellites du muscle squelettique [10,11]. Chez les plantes Vicia faba ou Triticum boeoticum aussi, des biais ont été observés dans la distribution des chromosomes marqués au préalable par un traceur radioactif puis révélés par autoradiographie après un certain temps d'incubation dans un milieu de culture dépourvu de radioactivité [12].…”
Section: Preuves Expérimentales De La Ségrégation Asymétrique Des Briunclassified
“…Moreover, premature senescence and the following loss of stemness during in vitro culture make the stable production of adult stem cells even more difficult (Lee et al, 2009). Unlike the conventional assumption that adult stem cells are free from the accumulated genetic mutation due to the existence of 'immortal DNA strand' (referred as 'immortal strand hypothesis') (Karpowicz et al, 2005;Rando, 2007), genetic alteration of adult stem cells during continuous in vitro culture was described (Sareen et al, 2009;Tarte et al, 2010). Thus, it is clear that there is a remote gap between the expectations of risk-free clinical application of stem cells including both pluripotent stem cells (hESCs and iPSCS) and adult stem cells and the current scientific circumstance of stem cells biology.…”
mentioning
confidence: 99%